Humanism according to Sufism - Dhary, Taghreed; Ali , Ali (Al-Adab Journal, 2024)
Sufism is a moral and spiritual mine with diverse components and multi-fields, and the spiritual and spiritual richness that the circle of Sufism bestows is what dissipates and destroys the castles of alienation that apply to man, by emphasizing the humanity of man in general and liberating him from all the restrictions of the reality of life. Man, according to Sufism, is an entity and an existence capable of being created. He is made and built as his body grows, just as his body grows on its own. His soul is capable of transcendence, even if it is cared for, just as the body is, just as the focus of the construction process in the entire existence is man. The importance of Sufism is evident in its call for coexistence and unity among people of different religions and sects within a single spiritual system, without paying attention to religious or ethnic affiliation. He works to unify them.